Tradução, adaptação transcultural e validação para o português brasileiro da escala da síndrome cognitivo afetiva do cerebelo (CCAS SCALE) - Scott, Stephanie Suzanne de Oliveira (2021)
The Cerebellar Cognitive Affective Syndrome (CCAS) is characterized by deficits in executive functions, language processing, spatial orientation and affect regulation in patients with cerebellar disease. The symptoms can occur isolated or along with motor and coordination symptoms. The CCAS assessment scale was developed in English and, to be used in other countries with inhabitants fluent in other languages, it must be translated and culturally adapted. The objectives of the study were to translate and cross-culturally adapt the Cerebellar Cognitive Affective Syndrome/Schmahmann Syndrome scale (CCAS) to Brazilian Portuguese; test the translated and adapted scale in the target population to ensure its reliability and reproducibility and validate the translated and adapted scale by applying it to the target population. Cross-sectional study carried out with patients with primary and secondary ataxia. The study included 111 individuals, aged between 20 and 80 years old, of both genders, 20 without cognitive and/or affective complaints who participated in the pre-test phase, 40 with cerebellar disease (hereditary/neurodegenerative ataxia or acquired/secondary cerebellar ataxia) and 51 healthy controls with no evidence of cognitive impairment and no affective symptoms and who were matched for sex, age (range 5 years) and educational level (≤8, 9-11, >11 years of education). The steps of translation and cultural adaptation were as follows: 1- Translation, 2- Translation synthesis, 3- Backtranslation, 4- Review Committee, 5- Pre-test, followed by validation and statistical analysis of the data, where association tests, mean comparison and ROC curve analysis were applied. In the association test, the items Semantic Fluency (>0.999), Phonemic Fluency (0.386) and Category Switching (0.253) did not present a statistically significant value when compared to the group of patients with the control group. Based on the analysis of the ROC Curve, optimal cutoff values were found for each sub-item of the scale. The Portuguese version and the results obtained with the validation are similar to the validation study in the American population. The scale has good internal consistency, is reproducible and has good reliability and has the potential to be a reliable tool for diagnosing and screening patients with CCAS, in addition to being useful in monitoring patients with cerebellar disease regarding cognitive symptoms.